RANCANGAN USER INTERFACE APLIKASI MOBILE SEBAGAI ALAT BANTU KOMUNIKASI VISUAL ANAK AUTISTIK UNTUK ICT WATCH - Tony; Hiryanto, Lely; Lie, Nadia Natha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ICT Watch as a community organization that focuses on collaborative building the capacity of Indonesian human resources for digital literacy knowledge and skills, online expression and cyber governance, has started its movement since 2002. ICT Watch works together with academics from LSPR Jakarta, Center for ASEAN Autism Research, UMN, Code Margonda, and KREAVI have developed a mobile application called VICARA (Visually Interactive Communication and Reading Aid) for autistic children. However, because there was no update, the application was taken down from the Apple Store and Google Play Store. Based on the evaluation results that have been carried out on the use of the VICARA application, ICT Watch intends to redesign and add updates and features to the VICARA application. The solution offered is the development of a user interface (UI) design for the VICARA application.